Studi Alokasi Belanja Modal Pada Anggaran Pemerintah Daerah Di Eks-Karesidenan Madiun - Hery Hermawan (JAMER : Jurnal Akuntansi Merdeka, 2020)
Abstract— This study aims to determine the effect of the level of effectiveness, independence, and fiscal decentralization on capital expenditures in districts/ city of Madiun Residency both partially and simultaneously. The type of research is quantitative research. Data analysis used is multiple linear regression, t test, F test and coefficient of determination. The result of this study show that, 1.The level of effectiveness significantly effect on the allocation of capital expenditure in the districts/city of Madiun Residency. 2. The level of independence significantly affects on the allocation of capital expenditure in the districts/city of Madiun Residency. 3. The level of fiscal decentralization significantly affects on the allocation of capital expenditure in the districts/city of Madiun Residency. 4. The level of effectiveness, independence, and fiscal decentralization simultaneously affect on the allocation of capital expenditure in districts/city of Madiun Residency. Keywords—: level of effectiveness;  independence; fiscal decentralization; capital expenditure.